Activation of formylmethanofuran synthesis in cell extracts of Methanobacterium thermoautotrophicum. - Bobik, T A (1989)
In cell extracts of Methanobacterium thermoautotrophicum, formylmethanofuran (formyl-MFR) synthesis (an essential CO2 fixation reaction that is an early step in CO2 reduction to methane) is subject to a complex activation that involves a heterodisulfide of coenzyme M and N-(7-mercaptoheptanoyl)threonine O3-phosphate (CoM-S-S-HTP). In this paper we report that titanium(III) citrate, a low-potential reducing agent, stimulated CO2 reduction to methane and activated formyl-MFR synthesis in cell extracts. Titanium(III) citrate functioned as the sole source of electrons for formyl-MFR synthesis and enabled this reaction to occur independently of CoM-S-S-HTP. In addition, CoM-S-S-HTP was found to activate an unknown electron carrier that reduced metronidazole. The activation of formyl-MFR synthesis by CoM-S-S-HTP may involve the activation of a low-potential electron carrier.